The Conspiracy in the Age of the Neoliberal Machine of Communication - Mizzau, Lorenzo (B@belonline, 2024)
Among the political phenomena that seem to attest to the crisis of neoliberal governance in the 21st century, conspiracism has assumed such prominence that there is increasing talk of a veritable golden age of conspiracy theories. While correctly noting the link between conspiracy theories and the hollowing out of the «political» triggered by globalization, political studies mostly stick to the assumption that conspiracy theories are a phenomenon of reaction to neoliberal societies. In my article, I seek to overturn this assumption by showing how conspiracism and the «new right» are, conversely, direct expressions of neoliberalism. To this end, I will trace a philosophical-political genealogy of conspiracism, framing it within the broader horizon marked by contemporary forms of the aesthetization and spectacularization of politics. Analyzing the nexus between politics, media and communication, I will try to show how the «neoliberal communication machine» structurally tends to promote what Furio Jesi called «right-wing culture».